Burnout and training satisfaction of medical residents in Greece: will the European Work Time Directive make a difference? - Pararas Nikolaos; Syrmos Nikolaos; Kolokythas Dimitrios; Tasoulis Athanasios; Keramaris Nikolaos C; Msaouel Pavlos; Thireos Eleftherios; Lionis Christos (BMC, 2010)
Abstract Background The aim of this study is to determine the prevalence of burnout in Greek medical residents, investigate its relationship with training satisfaction during residency and survey Greek medical residents' opinion towards the European Work Time Directive (EWTD). Methods A Multi-centre, cross-sectional survey of Greek residents was performed. The Maslach Burnout Inventory (MBI) was used to measure burnout, which was defined as high emotional exhaustion, combined with high depersonalization or low personal accomplishment. In addition, seven questions were designed for this study to evaluate self-reported resident training satisfaction and three questions queried residents' opinion on the EWTD and its effects on their personal and social life as well as their medical training. Univariate, bivariate and multivariate statistical models were used for the evaluation of data. Results Out of 311 respondents (77.8% response rate), 154 (49.5%) met burnout criteria and 99 (31.8%) indicated burnout on all three subscale scores. The number of residents that were dissatisfied with the overall quality of their residency training were 113 individuals (36.3%). Only 32 residents (10.3%) believed that the EWTD implementation will not have any beneficial effects for them. Conclusions Both burnout and training dissatisfaction were common among Greek residents. Systemic interventions are thus required within the Greek health system, aimed at reducing resident impairment due to burnout and at improving their educational and professional perspectives. Although residents' opinion on the EWTD was not associated with burnout levels, the EWTD was found to be predominantly supported and anticipated by Greek residents and should be implemented to alleviate their workload and stress.